2014
DOI: 10.1590/s0036-46652014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites Among Food Handlers in Western Iran

Abstract: Parasitic infection is one of the problems that affect human health, especially in developing countries. In this study, all of the fast food shops, restaurants, and roast meat outlets of Khorramabad (Western Iran) and all the staff employed by them, some 210 people, were selected through a census and their stools were examined for the presence of parasites. The parasitological tests of direct wet-mount, Lugol's iodine staining, formaldehyde-ether sedimentation and Trichrome staining techniques were performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
4
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 18 publications
(27 reference statements)
6
33
4
4
Order By: Relevance
“…In this study, the overall prevalence of intestinal parasites among food-handlers was 33% which is in consistence with the study conducted in Wolaita, Ethiopia (33.68%) [27] and comparable with the study done in Arba Minch, Ethiopia (36.0%) [28], Nigeria (38.1%) [29], Khartoum, Sudan (30.5%) [15]. The present prevalence is higher than 20.6%% in Hawassa University, Ethiopia [30], Western Iran (9%) [31], Sari, Northern Iran (15.5%) [32]. It was lower than the prevalence of 58.4% which was from Jimma, Ethiopia [25], 41.1% from Bahirdar Town [23] and 41.1% from Yebu Town, Ethiopia [20].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the overall prevalence of intestinal parasites among food-handlers was 33% which is in consistence with the study conducted in Wolaita, Ethiopia (33.68%) [27] and comparable with the study done in Arba Minch, Ethiopia (36.0%) [28], Nigeria (38.1%) [29], Khartoum, Sudan (30.5%) [15]. The present prevalence is higher than 20.6%% in Hawassa University, Ethiopia [30], Western Iran (9%) [31], Sari, Northern Iran (15.5%) [32]. It was lower than the prevalence of 58.4% which was from Jimma, Ethiopia [25], 41.1% from Bahirdar Town [23] and 41.1% from Yebu Town, Ethiopia [20].…”
Section: Discussionsupporting
confidence: 86%
“…One of the most important health indicators in each society is the prevalence status of parasitic diseases among its population [1,2]. Intestinal parasitic infections (IPIs) are among the most common causes of infections worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have shown that the transport of oxygen to the brain and decrease in blood stream may act as a mechanism in the complex etiology of AD (28). This study was conducted with regards to the localization of T. gondii tissue cysts in the central nervous system and reports indicating the impact of T. gondii on neurodegenerative diseases (7,9,10,13,16,29,30), as well as the lack of information about the prevalence of toxoplasmosis in patients with AD in studies conducted on the prevalence of parasitic infections in Lorestan province (18,19,(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%